Investigating the Awareness of Adolescence Education among Adolescents in Kerala: Exploring the Knowledge and Attitudes of Secondary School Students towards Adolescence Education in Kerala (Journal of Advances and Scholarly Researches in Allied Education, 2015)
This research aims to determine the knowledge and attitude about Adolescence Education awareness among Secondary school students in Kerala.The sample population for the study is the stage. In this stage a sample 120 students are selected to using stratified random sampling technique by giving importance to factors such as rural and urban Secondary School students.We observed poor baseline adolescence education awareness among secondary school students. Adolescents have poor baseline knowledge about growing-up changes and a health education intervention programme improves the knowledge and attitude among adolescents. Literature also shows that today’s adolescents have improper knowledge about their growing up which is obtained largely from inadequately informed friends, internet or movies. Most of the studies done on adolescents are about sexuality in girls or knowledge regarding HIV /STD.